IMPLEMENTASI LANJUTAN SMART DEVICE UNTUK SISTEM PRESENSI PERKULIAHAN BERBASIS WEB - Ardelia Astriany Rizky; Rina Kurniawati (INFOKOM (Informatika & Komputer), 2020)
The purpose of this research is to develop previous research, namely the implementation of smart devices in the lecture attendance system. In this study, we built a hardware device that can increase efficiency and develop a Lecturer Attendance System at Politeknik Piksi Ganesha. Where the Attendance Information System that was designed previously was still desktop-based and only used to input lecturer attendance only. The concept of Smart Devices is implemented in the form of a lecturer and student presence system using Radio Frequency Identification (RFID), which is a technology that can perform many-to-many communication, wireless data transmission compared to conventional barcodes that use optics. With these advantages, RFID technology can also be implemented as a supporting medium in the smooth running of the lecture process. The software development method used is SDLC (System Development Life Cycle). This information system of web-based lecture attendance uses PHP and MySql as database by making a reliable RFID reader. By using existing RFID technology, researchers built a special reader (custom) to make it easy for lecturers and students to carry out attendance activities, obtain information related to attendance and make it easy for academic officers to manage lecture administration reports for lecturers and students